Relationship of Academic Self-Management and Academic Anxiety Towards Academic Achievement of First Year Students In Institut Teknologi Bandung - Afifah, Rika; Pangestu, Aria Bayu (Syntax Idea, 2021)
This study aims to find the relationship of academic self-management and academic anxiety on academic achievement in first-year students at Institut Teknologi Bandung with quantitative methods on 111 samples of the first-year students. The results of the regression analysis showed that academic self-management and academic anxiety contributed 21.4% of students' academic achievement as measured by the Grade Point Average (GPA). Academic anxiety has a significant negative relationship to academic achievement, moreover, this study also found a significant difference in academic anxiety between students with low, moderate, and high academic achievement. Students with higher academic achievement have lower academic anxiety and vice versa. In first-year students at Institut Teknologi Bandung, the highest component of academic anxiety is the patterns of anxiety-engendering mental activity which indicates low student confidence and self-esteem. The findings of this research can be the basis for PeKa TPB Ministry of KM ITB in designing the character development program for the first-year students.